An essential role for the circadian-regulated gene Nocturnin in osteogenesis: the importance of local timekeeping in skeletal homeostasis - Guntur, Anyonya R. (2011)
The role of circadian proteins in regulating whole body metabolism and bone turnover has been studied in detail and has led to the discovery of an elemental system for timekeeping involving the core genes Clock, Bmal1, Per, and Cry. Nocturnin, a peripheral circadian-regulated gene has been shown to play a very important role in regulating adipogenesis by deadenylation of key mRNAs and intra-cytoplasmic transport of PPARγ. The role that it plays in osteogenesis has previously not been studied in detail. In this report we examined in vitro and in vivo osteogenesis in the presence and absence of Nocturnin and show that loss of Nocturnin enhances bone formation and can rescue Rosiglitazone induced bone loss in mice. The circadian rhythm of Nocturnin is likely to be an essential element of marrow stromal cell fate.